2019
DOI: 10.1103/physrevlett.123.027201
|View full text |Cite
|
Sign up to set email alerts
|

Novel Strongly Spin-Orbit Coupled Quantum Dimer Magnet: Yb2Si2O7

Abstract: The quantum dimer magnet (QDM) is the canonical example of quantum magnetism. The QDM state consists of entangled nearest-neighbor spin dimers and often exhibits a field-induced triplon Bose-Einstein condensate (BEC) phase. We report on a new QDM in the strongly spin-orbit coupled, distorted honeycomb-lattice material Yb2Si2O7. Our single crystal neutron scattering, specific heat, and ultrasound velocity measurements reveal a gapped singlet ground state at zero field with sharp, dispersive excitations. We find… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 47 publications
(34 reference statements)
0
21
0
Order By: Relevance
“…Note that these data, as well as data collected at additional field strengths, are also shown and discussed in detail in Ref. [13].…”
Section: Powder X-ray Diffraction and Lauementioning
confidence: 76%
See 2 more Smart Citations
“…Note that these data, as well as data collected at additional field strengths, are also shown and discussed in detail in Ref. [13].…”
Section: Powder X-ray Diffraction and Lauementioning
confidence: 76%
“…Large, clear single crystal pieces (≈15 mm) of C-Yb 2 Si 2 O 7 were prepared from micro-pulling-down (µ-PD) technique to fabricate components for near-infra red scintillators in medical applications [12]. While studies on magnetic properties of Yb 2 Si 2 O 7 were non-existent until the recent discovery of quantum dimer magnet by our group [13], the electronic structure of C-Yb 2 Si 2 O 7 has been studied in brief using X-ray photoemission spectroscopy [14] and valence electron energy-loss spectroscopy [15]. The existence of an isolated energy level in the band gap of Yb 2 Si 2 O 7 was identified in the latter report.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is usually in the context of single ion physics, and the crystalline environments may change the electronic properties of the rare-earth ions considerably. Experimental hallmarks of exotic quantum states have been recently reported in a number of Yb-based (4 f 13 ) compounds by the observation of Tomonaga-Luttinger liquid behavior and spinon confinement-deconfinement transitions in YbAlO 3 [13]; spinon continuum and spinon confinement in Yb 2 Pt 2 Pb [14,15] and in the triangular-lattice systems YbMgGaO 4 [16,17]; the quantum dimer magnet state in Yb 2 Si 2 O 7 [18] and a Higgs transition from a magnetic Coulomb liquid to a ferromagnet in Yb 2 Ti 2 O 7 [19]. In the rare-earth orthoferrite YbFeO 3 the Yb magnetic sublattice also exhibits rich quantum spin dynamics [20].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] BaCuSi 2 O 6 is a quasi-2D square lattice magnetic insulator with a gapped spin dimer ground state and is supposed to be an ideal candidate for studying the BEC of triplons as a function of the external magnetic eld. 6 Recently, Hester et al 7 reported a new Yb 3+ based QDM in the distorted honeycomb-lattice material Yb 2 Si 2 O 7 with strong spin-orbit coupling (SOC). The intradimer bond length of two Yb ions is about 3% shorter than that of the inter-dimer ones, resulting in contrastive exchange interactions J intra ¼ 0.236 meV and J inter ¼ 0.06 meV.…”
Section: Introductionmentioning
confidence: 99%